Community and local governance for peace and development in Nepal - Vidyadhar Mallik (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Nepal is currently experiencing a political stalemate as its Constituent Assembly (CA) could not write a constitution and its extended four-year term ended prematurely following a court ruling due to a lack of political consensus (on issues of state restructuring and form of governance). The peace process has yet to reach a satisfactory conclusion after a decade of war waged by Maoists. Presently, Nepal's caretaker government aims to hold new CA elections, whereas the opposition is asking for the prime minister's resignation. Overall, governance is deteriorating, there is diminishing accountability and service delivery is failing. Moreover, the central government is increasingly failing to reach out to citizens living in the periphery. Some politicians and opinion-makers see the increase in political aspirations of various ethnic groups (especially those related to ethnic federalism and a socio-economic restructuring of the state) as a cause of the current crisis and blame those who have mobilised demands for inclusive democracy. Economic growth has been slow – the peace process did not provide any substantial peace dividends. The local governments (LGs) are losing their legitimacy – as they are not elected – and there are increasing allegations of corruption within the transitional structures. Still, mechanisms of local and community governance are very important elements for Nepal's transition to sustained peace. Nepal has more than 50,000 community organisations (COs) and about 4,000 local and municipal governments. Community-based development initiatives, despite their challenges, are often effective in socialcapital formation, providing employment, creating local infrastructure and peace-building. Reforms aiming to empower the communities and raise their awareness level have been satisfactory. LGs, despite their internal disarray, are creating more and more citizen forums and COs for this purpose. Strengthened LGs and COs can complement the overall situation of peace and development by expanding social capital and applying the principles of good governance. They can help smooth the way during the current transition process and absorb the shocks of uncertainties from the state-restructuring process in Nepal. But the current programmes for strengthening local and community governance are facing serious challenges in their implementation. They suffer from gaps in credibility and the lack of commitment from politicians and bureaucrats. There are also issues of poor linkage and coordination between various levels and agencies as well as a lack of empathy and outreach towards the citizens. A numberof reforms are required to improve the overall governance situation in Nepal and make the LGs and COs more effective. Important reforms are: Local governance reforms: immediate elections for LGs, even if it is only for a transitional period; planning and budgeting of LGs linked with demand mobilization of citizens, fiscal transparency throughpublic hearings and budget education; inclusion of diverse ethnic and disadvantaged groups in government structures through affirmative action programmes. Compact with people: strengthen ward citizen forums and community organisations; enact a law for community empowerment; discourage politicization of community organisations; invest more in social mobilisation. Peace and development framework: conflict-sensitive approaches to development; development works for conflict-affected areas; plan for faster and inclusive economic growth.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten